Devastating coagulase-negative staphylococcal septicaemia in an extremely low birth weight infant. (27th November 2012) - Samarasekara, Sujeevan Indunil; Booth, David; Clarke, Paul
Abstract : In developed countries, coagulase-negative staphylococci (CoNS) are responsible for the majority of late-onset infections in very low birth weight infants undergoing neonatal intensive care. As a common skin commensal, they are often considered as mere contaminants of peripheral blood cultures or as relatively benign bacteria clinically. We present a case of invasive CoNS septicaemia in an extremely low birth weight infant which had devastating effects.